Flocculant Assisted Treatment of Suspended Sidoarjo Mud - Thilal Syihabuddin; Januarti Jaya Ekaputri; Chikako Fujiyama (Postgraduate, University of Mataram, 2025)
This study investigates the use of lime-based flocculants as a treatment method for Sidoarjo mud (LUSI) to improve solid–liquid separation and reduce the environmental impact of its discharge into the Porong River. Several commercial lime-derived flocculants were tested through jar experiments to evaluate their effectiveness in promoting particle aggregation and enhancing settling behavior under conditions similar to the existing treatment pond. The results indicate that a mud-to-water ratio of 1:4 provided the most efficient sedimentation performance, reflected by faster settling rates and clearer supernatant. Among the flocculants examined, differences in chemical composition and particle morphology influenced the degree of aggregation and overall clarity of the treated water. The treatment substantially reduced turbidity and suspended solids, while also lowering chloride levels in the clarified water. These findings suggest that lime-based flocculants are a feasible option for mitigating the environmental burden of LUSI mud disposal by improving separation efficiency.